2009
DOI: 10.1002/hep.22655
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance is a risk factor for esophageal varices in hepatitis C virus cirrhosis†

Abstract: P ortal hypertension (PH), defined by a hepatic venous pressure gradient (HVPG) greater than 6 mmHg, 1 is a common complication of cirrhosis. The presence and the development of esophageal varices (EV) is a clinical manifestation of PH, 2,3 with a prevalence that can range from 40% to 80% in patients with cirrhosis. This prevalence increases progressively in relation to the severity of liver damage. 4,5 The presence of EV is also a clear indicator of a certain stage of cirrhosis. 6 The development of EV in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
70
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 49 publications
7
70
1
1
Order By: Relevance
“…The difference between our study and that of Camma` et al, 2009 is that none of our patients were diabetics and whey the IR was higher in their study than ours may agree with the view of Dogru et al, 2009 in their comment on the study of Camma` where we noticed that most of the study participants were overweight and some of them were even obese. Obesity is a strong risk factor for DM and also for IGT (impaired glucose tolerance).…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…The difference between our study and that of Camma` et al, 2009 is that none of our patients were diabetics and whey the IR was higher in their study than ours may agree with the view of Dogru et al, 2009 in their comment on the study of Camma` where we noticed that most of the study participants were overweight and some of them were even obese. Obesity is a strong risk factor for DM and also for IGT (impaired glucose tolerance).…”
Section: Resultssupporting
confidence: 76%
“…Also, Emam et al, 2009 reported a diagnostic sensitivity of (98%) with specificity of (64%), positive predictive value of (83%), negative predictive value of (94%) and accuracy of (86%) for the predictor platelet count/spleen diameter ratio. In this study, we did evaluate the predictor introduced by Camma` et al, 2009 which is the association of IR, regardless of diabetes, with the presence of O.V. None of our 124 patients was found to be diabetic.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus it has been suggested that IR has a negative impact on the response rates to interferon-based therapy in chronic hepatitis C virus infection (19) and that IR could be a predictor of the presence of PH in patients with nonalcoholic fatty liver disease (16). Furthermore, a recent published clinical study has suggested that IR is able to independently predict the presence of gastroesophageal varices in cirrhosis (11). The authors attributed this effect to a possible pathophysiological link between IR and PH.…”
mentioning
confidence: 99%
“…We read with great interest the article by Cammà et al 1 reporting the potential usefulness of insulin resistance (IR) combined with platelet count/spleen diameter ratio as simple, noninvasive, and easy-to-get tests for predicting esophageal varices (EVs) in patients with Child A cirrhosis caused by hepatitis C virus (HCV). We would like to draw attention to similar studies on IR combined with platelet count/spleen diameter ratio in predicting EVs in cirrhosis, not just in Child A HCV cirrhosis.…”
Section: Insulin Resistance and Platelet Count/spleen Diameter Ratio:mentioning
confidence: 99%